Revised and Extended Analysis of Ar vi - C. J. B. Pagan; M. Raineri; M. Gallardo; J. Reyna Almandos (The Astrophysical Journal Supplement Series, 2023)
This paper analyzes the emission spectrum of Ar vi and adds new information about this ion. We use a capillary light source to study the Ar vi spectrum, presenting 39 line classifications for the first time, including one line in the ultraviolet region. A total of nine possible Ar vi lines in the ultraviolet between 3288 and 3440 Å are analyzed. We revised the wavelengths of the lines at 1284.01 and 1307.42 Å previously used to identify Ar vi in astronomical objects. The lifetimes, weighted transition rates ( gA ) and their estimated uncertainties, and cancellation factors are obtained using a Hartree–Fock calculation with energy parameters adjusted to fit the values of the experimental levels and modified to include core polarization effects. We analyze all the experimentally known transitions of the Ar vi spectrum, with particular attention to conflicting information. Isoelectronic sequences of energy levels and transitions, for which the trend is not a smooth curve, are analyzed. We revise previous studies where the information needed to support line classifications and level designations is incomplete.